Public Service Motivation and Practical Implications in the Higher Education Sector - Hikmat Hikmat; Halimah Abdul Manaf; Sirikanya Seti; Evi Satispi; Izzatusholekha Izzatusholekha; Maya Puspita Dewi (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
The purpose of this study is to discuss the concept of public service motivation (PSM) among lecturers in tertiary institutions. This study focuses on studying how existing literature represents the understanding of faculty members about PSM in the context of higher education. The method used in this study is the systematic review method, which is a comprehensive review driven by protocols and data synthesis that focuses on a topic or related key question. PSM has a significant positive impact on higher education and public services. PSM has a positive effect on public services, learning experiences, and community development. The results of this study provide a detailed understanding of PSM and their significance in the field of higher education. Furthermore, the implications of these findings will be discussed in relation to the direction of future research and practical implications for the higher education sector. The period of implementation of this research will depend on the number of papers analyzed and the complexity of literature synthesis.Keywords: Motivation of public services, Higher education, Systematic review